Treatment choice in mild to moderate sleep apnoea in the European Sleep Apnea Database - Fridriksson, Benedikt; Hedner, Jan; Zou, Ding; Verbraecken, Johan; Schiza, Sophia; Basoglu, Ozen K.; Testelmans, Dries; Joppa, Pavol; Dogas, Zoran; Mihaicuta, Stefan; Saaresranta, Tarja; Ludka, Ondrej; et al. (European Respiratory Society (ERS), 2026)
Introduction: In mild to moderate obstructive sleep apnoea (OSA), positive airway pressure (PAP) and mandibular advancement devices (MADs) are recommended treatments according to guidelines. This cross-sectional study aimed to determine the clinical and organisational predictors for treatment recommendations in mild to moderate OSA.
Methods: In the European Sleep Apnea Database, factors predicting the choice of MAD or PAP treatment were determined in patients with newly diagnosed mild to moderate OSA. Accessibility and reimbursement of MADs study sites was obtained via questionnaire. The regression model included anthropometrics, Epworth Sleepiness Scale score, OSA severity, MAD accessibility and reimbursement, and a comorbidity index variable.
Results: 6618 (65.5%) patients received PAP and 3491 (34.5%) were recommended MADs. MAD recommendations varied between centres (0% to 76%). Significant factors favouring MADs include mild versus moderate OSA (odds ratio 6.0, 95% CI 5.3-6.8), negligible versus moderate intermittent hypoxia (OR 2.0, 95% CI 1.7-2.4), no versus excess daytime sleepiness (OR 2.6, 95% CI 2.1-3.1), a comorbidity index score of 0 compared to 3 or more (OR 3.8, 95% CI 3.1-4.6) and no insomnia diagnosis versus diagnosed insomnia (OR 2.0, 95% CI 1.7-2.4). MAD accessibility and reimbursement predicted MAD treatment recommendations (OR 2.3, 95% CI 1.8-2.9 and OR 1.5, 95% CI 1.4-1.7, respectively).
Conclusion: In mild to moderate OSA, MADs are less frequently recommended than PAP, particularly amongst patients with a higher disease burden. MADs were more frequently used when they were more accessible and reimbursed. Thus, MADs are likely an underused treatment in mild to moderate OSA.